Construction and Semantics of Idioms with Colors in Mu'jam at-Ta'bir al-Ishthilahi fi al-Arabiyat al-Mu’ashirah - Damhuri, Damhuri; Bahri, Ratni Bt. Hj.; Mokodongan, Satriana (Institut Agama Islam Negeri (IAIN) Kendari, 2024)
This study presents information about the meaning of connotations, grammatical construction, and semantic categories of color idioms in Arabic. Through library research, the main data source is Mu'jam at-Ta'bir al-Ishthilahi. Data collection techniques are reading techniques and note-taking techniques. The determining element sorting technique is used to analyze the data. The results of this study show that white and black are the dominant elements in forming Arabic idioms, followed by yellow, green, and red. White color is dominated by positive connotations, although there are uses with negative and neutral connotations. In contrast, black is dominated by negative connotations, and there is one data with positive and neutral connotations. The colors yellow and green only have negative connotations. Meanwhile, red has both positive and negative connotations. There are full and partial idioms in terms of the meaning of the forming elements. In terms of grammatical construction, there are three categories: First, N + Adj. The colors in this construction are all attribute elements. Second: Intransitive verb + N, which is one case. Third: V + Preposition 'ala + Adjective, which is one case. Fourth: Verb + preposition + Adjective + conjunction + adjective, which is one case. The implication is that color symbolization is closely related to people’s perceptions. In Arab society, giving connotations to black is more dominant as a negative or white as a positive symbol. However, color connotations are not closed. The connotation of a particular color is closely related to the language user's perception of the object.